2023
DOI: 10.1155/2023/9164883
|View full text |Cite
|
Sign up to set email alerts
|

Rosa laevigata Michx. Polysaccharide Ameliorates Diabetic Nephropathy in Mice through Inhibiting Ferroptosis and PI3K/AKT Pathway-Mediated Apoptosis and Modulating Tryptophan Metabolism

Tianyu Zhang,
Wenjuan Sun,
Lixin Wang
et al.

Abstract: Diabetic nephropathy (DN) is a metabolic disease wherein chronic hyperglycemia triggers various renal cell dysfunctions, eventually leading to progressive kidney failure. Rosa laevigata Michx. is a traditional Chinese herbal medicine. Many studies have confirmed its antioxidative, anti-inflammatory, and renoprotective effects. However, the effects and mechanisms of Rosa laevigata Michx. polysaccharide (RLP) in DN remain unclear. In this study, a DN mouse model was established to investigate the therapeutic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Many plant polysaccharides extracts and monosaccharides have certain anti‐inflammatory effects on the skin barrier. 15 , 16 , 17 , 39 , 40 Wound healing and repair involve individual and collective cellular migration processes. 41 We found that PURP at concentrations ranging from 1 to 500 µg/mL had no cytotoxic effects, with cell viabilities greater than 100% (Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Many plant polysaccharides extracts and monosaccharides have certain anti‐inflammatory effects on the skin barrier. 15 , 16 , 17 , 39 , 40 Wound healing and repair involve individual and collective cellular migration processes. 41 We found that PURP at concentrations ranging from 1 to 500 µg/mL had no cytotoxic effects, with cell viabilities greater than 100% (Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%